Flipped classroom in history learning to improve students’ critical thinking - Muhammad Rijal Fadli; Saefur Rochmat; Ajat Sudrajat; Aman Aman; Arif Rohman; Kuswono Kuswono (Institute of Advanced Engineering and Science, 2022)
The flipped classroom is very helpful for students to understand learning material, but it is still very minimally used, especially in history learning. This study analyzed the effect of the flipped classroom model in history learning to improve students' critical thinking. This study employed a quasi-experimental non-equivalent control group design, by dividing into two class groups, namely experimental and control. The sample was 121 students who were selected through cluster random sampling technique. The data collection was through observation, interviews, and instruments in the form of critical thinking tests. Data analysis used an independent sample t-test and N-gain score test to analyze the effect of a flipped classroom in history learning to improve critical thinking. The results showed that the flipped classroom in history learning had a significant effect on improving students' critical thinking skills as evidenced by the independent sample t-test test with a significance value of 0.000<0.05, and the N-gain score test which was included in the moderate criteria. So, the flipped classroom model in history learning is very suitable to be used and implemented. Hence, learning objectives are achieved so that history learning can run well and optimally.